Analisis Peran Otoritas Jasa Keuagan (OJK) Sumatera Barat dalam Mengawasi Kepatuhan Bank Syariah - Bella Nikita; Harfandi Harfandi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
In order to ensure sharia bank operations comply with sharia law and related banking regulations, this research was inspired by the role of the Financial Services Authority (OJK) in West Sumatra in supervising sharia banks' compliance with sharia regulations and the principles of effective supervision. The purpose of this research is to determine the extent of the role of the West Sumatra OJK in carrying out supervision in ensuring that Islamic banks comply with regulations relevant to their operations. This research uses written research with a qualitative approach. Written research is research conducted indirectly or interviews conducted virtually. Research conducted by utilizing technology and online resources conducted directly or face-to-face such as interviews, data collection, or access to information sources conducted online or via online platforms. In this research, the researcher gave questions to the staff of the OJK Bank Supervision office which were sent via OJK email which would later be answered indirectly (online). The object of this research was carried out at the West Sumatra OJK Office which is located at Jl. Khatib Sulaiman No. 68 Ulak Karang Selatan, North Padang District, Padang City, West Sumatra 25137. The following are the results of inspections carried out at the West Sumatra Financial Services Authority (OJK): 1) The West Sumatra Province Financial Services Authority (OJK) has the ability to assess and guarantee Sharia Banks in carrying out their operations. Its operations are in accordance with sharia principles. This is achieved through off-site monitoring and analysis of reports. Either through field supervision or direct OJK audit findings, or through submission of audit results by the bank. The aim is to protect the stability of the financial system, prevent risks that are detrimental to the economy, and ensure the security of customers’ trust in banking. Through OJK supervision, it will have an impact on the effectiveness of implementing sharia principles in operations, which will ultimately have an impact on improving the performance of sharia banks. 2) In order to ensure Sharia Banks comply with regulations, the West Sumatra Financial Services Authority (OJK) follows the values contained in supervision, including ideas for improving supervision now and in the future. Integrity, accountability, fair treatment, availability of information and reporting, effectiveness, adaptation, and cooperation between institutions and society are qualities that are included in the context of supervisory value.